Thermal systems management and heat exchangers. (SP (Society of Automotive Engineers), 2001)
Collection of papers from the "Thermal Systems Management" sessions of 2001 SAE World Congress, held March 5-8 in Detroit, Michigan. Papers cover analysis of the components, CFD modeling, and simulation of the components and systems to provide engineers with insights for designing better and more efficient components and thermal systems. Paper topics include: thermal modeling of engine components for temperature prediction and fluid flow regulation; airflow parameters near the differential of a rear drive passenger car; thermal analysis of electric motors in engine cooling fan systems; exhaust heat recovery system for modern cars; integrated cooling systems for passenger vehicles; experimental study of heat transfer from the heated rib-roughed wall to a steady or pulsating flow; performance prediction of a laminate evaporator with hydrocarbon refrigerants as the working fluids; and water condensate retention and "wet" fin performance in automotive evaporators.